Mapping of Responses to Tunisian Islamic Family Law Issues; Regulatory Study of Equal Inheritance Rights of Men and Women - Auliya Ghazna Nizami (Al Ahkam, 2022)
This article discusses the issue of equal inheritance rights between men and women which has long been the subject of discussion in Islamic inheritance studies. It is interesting because the discussion focuses on the context of the Tunisia which is known to have a progressive positive law. This is reinforced by the existence of a draft amendment proposal to Article 146 of Majallah al Aḥwāl Asy Syakhṣiyyah (MAS) with the title Aḥkām Tata'allaqu bi at Tasāwiy fī al Mīrāṡ. This article aims to map the responses that emerged from the proposed amendment to article 146 of the MAS, the motivation behind the responses, and the implications for efforts to equalize the rights of men and women in inheritance in Tunisia. Comparative approach used in this article, which is supported by historical and political studies to deepen the findings. The death of Beji Caid Essebsi is considered the main factor in the stagnation of the legal process for the amendment of Article 146 MAS, in addition, the strong response from conservative groups who do not agree with the amendment also has a big impact. This is reinforced by the statement of the current government of Tunisa which tends to stick more to the principles of Conservative Fiqh and views the proposal as a violation of Islamic law (sharia).